PEREMPUAN; ANTARA NORMA DAN REALITA - Duski Samad (Kafa`ah: Journal of Gender Studies, 2013)
Women are the pillar of state. The women have existence in dynamics of the community in the world. Throughout human history, women function and existence   is not always be well and nice. Sometimes they have unwell position, seems at of Roman, Greek, Egyptian history. Some effort provides women's rights are done continually, either in the field of legal protection or religious, social and cultural. Rule of law, religious, social and cultural hardly be effective without any effort and strong will of the policy makers and all to make it happen. Keywords : Women, protection, discrimination, religion, socio culturalCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i1.65